2021
DOI: 10.33394/jollt.v9i2.3533
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Writing Through Canva Application

Abstract: This study aims to investigate the effectiveness of using Canva application media to enhance students’ writing skills. This research was conducted in July-August at Mts Al-Islamiyah, Ciledug. Researchers used a quantitative method which is pre-experimental research design by applying pre-test and post-test. Writing tests were employed in collecting students’ achievement as instruments of this study. Researchers used one class in class IX-1 MTs Al-Islamiyah Ciledug as research samples. Determining samples of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 19 publications
5
25
0
2
Order By: Relevance
“…A growing number of studies have started to consider the role of Canva in teaching and learning practices. Hadi et al (2021) suggested that using learning media such as digital posters and online presentations can help increase students' interest, creativity, and drive to learn writing skills. A recent study conducted by Yundayani et al (2019) investigated the effect of Canva on students' writing skills.…”
Section: Canva As a Tool To Create Learning Mediamentioning
confidence: 99%
“…A growing number of studies have started to consider the role of Canva in teaching and learning practices. Hadi et al (2021) suggested that using learning media such as digital posters and online presentations can help increase students' interest, creativity, and drive to learn writing skills. A recent study conducted by Yundayani et al (2019) investigated the effect of Canva on students' writing skills.…”
Section: Canva As a Tool To Create Learning Mediamentioning
confidence: 99%
“…Sebagaimana klaim dari provider Canva, aplikasi ini memberikan kemudahan dalam pengoperasiannya dengan berbagai cara dan juga menyediakan berbagai format elemen media yang menarik dan interaktif. Platform yang memungkinkan kerja kolaboratif dan dibagikan ke berbagai platform yang berbeda menjadikan pengguna mudah dalam mengelola aktivitas [13]. Meski aplikasi ini tidak spesifik untuk pendidikan, namun pengelompokan layanan sesuai bidang menjadikan pengguna mudah melakukan customisasi media yang akan dibuat [14].…”
Section: Kelompok Element Yang Digunakan Text Shape Gambarunclassified
“…Even though narrative text is among the easiest one to write, however, the Indonesian high school students still have difficulty in developing their ideas and organizing them into good sentences and paragraphs (i.e. Karmila, 2017;Megawati & Anugerahwati, 2012), they lack of ideas to write (i.e., Hadi, Izzah & Paulia, 2021), they do not understand how to apply generic structure and language features (i.e., Syarifah & Emiliasari, 2019), and they do not have enough vocabulary in English (i.e., Alisha, Safitri & Santoso, 2019).…”
Section: Introductionmentioning
confidence: 99%